2018
DOI: 10.1364/osac.2.000083
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of a graphene-polyimide hybrid electro-optical liquid crystal device

Abstract: A planar liquid crystal (LC) cell is designed by placing together a monolayer graphene coated glass slide and a planar-aligning polyimide layer on an indium tin oxide (ITO) coated glass slide. It is shown that the monolayer graphene film on one side of the cell can serve as the planar-alignment agent. At the same time, the monolayer graphene film also functions as the transparent electrode. The successful optical and electro-optical operations of this hybrid LC cell with monolayer graphene on one side and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…This interaction is further characterized by the π-π electron stacking interaction with a binding energy ranging from 0.74 to 0.88 eV/molecule [31], which is attributed to a significant amount of charge transfer from the NLC molecule to the honeycomb pattern of the carbon atoms. Supporting this, the previous findings of Basu et al [27,32,33] demonstrated that graphene can serve as the planar-alignment agent for an NLC due to this specific graphene-NLC interaction.…”
Section: Introductionsupporting
confidence: 65%
“…This interaction is further characterized by the π-π electron stacking interaction with a binding energy ranging from 0.74 to 0.88 eV/molecule [31], which is attributed to a significant amount of charge transfer from the NLC molecule to the honeycomb pattern of the carbon atoms. Supporting this, the previous findings of Basu et al [27,32,33] demonstrated that graphene can serve as the planar-alignment agent for an NLC due to this specific graphene-NLC interaction.…”
Section: Introductionsupporting
confidence: 65%
“…Therefore, this nano-architectural symmetry between the hexagons in both these species leads to an epitaxial interaction between them, and the benzene rings of the LC coherently align on the hexagonal lattice of h-BN [46]. This type of epitaxial interaction also exists between the nematic LC and the hexagonal lattice of other different nanomaterials, such as graphene [47][48][49][50][51][52][53][54][55] and carbon nanotube [56,57]. This spontaneous alignment mechanism of the LC on the hexagonal lattice is the fundamental principle behind designing the LC cell employing the 2D h-BN as a planar-alignment agent.…”
Section: Fabrication Of the 2d H-bn Based Lc Devicementioning
confidence: 99%